Аналтэм сяська: повесть / Геннадий Мадьяров - Мадьяров Геннадий Михайлович (Удмуртия, 1994)
Экземпляры: ХР (20180510) / Инвентарный номер: 33800 / Цена: 0.50 / Сис.шифр: С(Удм) / Авт.знак: М 33 / ГРНТИ: 17.82.31 / ББК: С(Удм)